Pemimpin Inovatif Dalam Manajemen SDM : Membangun Budaya Inovasi yang Berkelanjutan - Gunawan, Gempa; Nasution, Zulhasby Assidqy; Aljuned, Raihani Azzahra; Suwifania, Jihan; Suhairi, Suhairi (CV. Pusdikra Mitra Jaya, 2024)
Currently, technological developments in globalization are starting to give birth to new ways of completing several jobs in various sectors. Starting from manufacturing, services, to the banking business. This makes conditions demanded in various sectors through types of human resources that have competitiveness and are creative. It is intended that if the government sector receives human resources who do not have creativity and there is no innovation as a provision, it will cause the performance of an organization to not develop, and give everyone a negative stigma towards the government agency sector. Therefore, it is highly demanded aspects in competing to show the best in order to lead to good performance. Talking about innovation, innovation is a very much confused thing according to the positive side. Innovation is born from the existence of a creativity and curiosity in order to give birth to new studies.